To Harvest or Not to Harvest? An Analysis of Cutting Behavior on Federal Timber Sales Contracts - Rucker, Randal R.; Leffler, Keith B. (The Review of Economics and Statistics, 1988)
Randal R. Rucker, Keith B. Leffler, To Harvest or Not to Harvest? An Analysis of Cutting Behavior on Federal Timber Sales Contracts, The Review of Economics and Statistics, Vol. 70, No. 2 (May, 1988), pp. 207-213